Skull Anatomy of the Miniaturized Gecko Sphaerodactylus roosevelti (Squamata: Gekkota) - Abdala, Virginia Sara Luz (2008)
A detailed description of the skull and jaw of the gecko Sphaerodactylus roosevelti is presented. The bones are described articulated and isolated with special consideration given to the type of suture among joining elements. S. roosevelti was compared with 109 gekkotan species to evaluate the osteological variation and to find characters for cladistic analysis. Changes in the skull associated with the miniaturization process are discussed within the sphaerodactylid geckos. A noticeable increase of overlapping sutures was observed in the snout of the smallest sphaerodactylids compared to other gekkotans. This pattern is convergent with that in miniaturized pygopodids and may be attributed to adaptations for decreasing mechanical resistance of the cranium during feeding or burrowing. New cranial characters support Sphaerodactylinae as a monophyletic group and should be useful for resolving questions such as their relationship with other gekkotans.